Comparative study of lipid profile in smokers, tobacco chewers and diabetic patients - Yadav, B.K.; Bade, A.R.; Singh, J.; Jha, B. (Journal of Institute of Medicine Nepal, 2007)
Background: Smoking, tobacco chewing and Diabetes mellitus have been well recognized risk factors for arteriosclerosis. This study was conducted to find out the effect of these factors on lipid profile in Nepal. Method: Serum lipid profile was Studied In 29 smokers, 13 tobacco chewers, 22 diabetic patients and 29 controls le. non smokers, non tobacco chewers and non diabetic individuals. Results: The mean serum total cholesterol (4.8±0.9 mmol/ltr) was significantly higher in smokers than in non smokers (p<0.01).Mean low density lipoprotein (LDL) cholesterol (3.2±0.8mmol/itr) and triglyceride (2.0±0.9mmol/itr) were significantly higher in smokers (p<0.005, p<0.05 respectively) whereas mean high density lipoprotein (HDL) cholesterol (0.77±0.18mmol/Itr)was significantly lower (p<0.05). Tobacco chewing was related to higher total cholesterol (p<0.005), higher LDL cholesterol (p<0.05) and higher triglyceride (p<0.05) levels. There was no significant difference in HDL cholesterol level, The diabetics had higher values of total cholesterol (5.0±0.9mmol/Itr) and triglyceride (2.1±0.8mmol/Itr) levels (p=0.000 and p<0.01 respectively) than controls. However, there were no significant differences in HDL cholesterol and LDL cholesterol levels. Conclusion: A moderate portion of the effect of cigarette smoking, tobacco chewing and Diabetes mellitus on risk of cardiovascular risk may be explained by an adverse effect of these on blood lipids. Journal of Institute of Medicine Vol.27(3) 2005